A framework for institutional determinants of sustainable growth in Sub-Saharan Africa - Rowjee, Priya (My University, 2015)
ABSTRACT At the start of the new millennium, Sub-Saharan Africa’s development prospects have experienced a sea change. Economic performance over the past decade has surpassed any previous period, and the region is now the second-fastest growing in the world. With a projected collective GDP of US$2.6 trillion in 2020, a growing consumer base and labour force, growth in consumer-facing industries, increased international trade and improving business environment, Africa has made its rise heard on a global scale. Investors and business executives are increasingly looking to Africa to achieve their next growth frontier. However, investment into Africa is still being approached with “cautious optimism”. In addition, previous investment into Africa was dominated by the resource-seeking motive, with little attention being paid to the newly relevant market-seeking motive. Further, Africa cannot be viewed in a homogenous light; rather countryspecific analysis focused on growth sustainability is required to appropriately understand market opportunities. The purpose of this research was to construct a framework to enable the analysis and classification of the institutional context of various Sub-Saharan African countries, as a means to understand growth sustainability. The framework was derived from the application of Acemoglu and Robinson’s (2012) notion of inclusive versus extractive political and economic institutions. The framework was qualitatively validated and stress-tested through a series of select expert interviews. The key findings demonstrated that the sustainability of a country’s growth is a function of its institutional context, which also influences the marketseeking FDI decision process. In particular, companies are more likely to invest market-seeking FDI into a country that demonstrates a sustainable growth trajectory; as attained under an inclusive institutional context. Companies could thus utilise this framework as an additional reference point when making their market-seeking FDI decision pertaining to Sub-Saharan Africa, providing them with a rigorous and consistent methodology to the market entry decision process.
MBA 2014
Keywords: Economic development, International business enterprises , Foreign Investments,Sustainable development